2020
DOI: 10.31224/osf.io/8mf46
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Energy justice, built environment and poverty: A deep-narrative analysis of energy cultures in Brazil, India and Nigeria for policy modelling

Abstract: Distributive energy justice as a policy instrument is crucial to meet UN-SDG 7 targets at the poorest section of rapidly urbanising Global South. This study mobilised this policy instrument to derive poverty alleviation focal points across slum rehabilitation housing in Brazil, India and Nigeria. It emphasises on the social dimensions of energy services which currently remains a literature gap. The core methodological innovation lies in the nested deep narrative analysis approach using topic modelling and grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The objective of topic modelling is to extract latent semantic topics from large volumes of textual documents (i.e., corpora). LDA is a widely used topic modelling (TM) technique, with recent applications spanning across political science and rhetoric analysis (8)(9)(10)15,16), disaster management (12,17,18) and public policy (13,14,19). The analysis consisted of three main steps.…”
Section: Data Collection and Pre-processingmentioning
confidence: 99%
See 1 more Smart Citation
“…The objective of topic modelling is to extract latent semantic topics from large volumes of textual documents (i.e., corpora). LDA is a widely used topic modelling (TM) technique, with recent applications spanning across political science and rhetoric analysis (8)(9)(10)15,16), disaster management (12,17,18) and public policy (13,14,19). The analysis consisted of three main steps.…”
Section: Data Collection and Pre-processingmentioning
confidence: 99%
“…This study aided in understanding the polarising shifts in policy interventions that modulated the political narratives in Germany. More recent applications of TM includes crisis identification in urban areas for evidence-based policymaking (12), deep narrative analysis for deriving intervention points for distributive energy justice in poverty (13) and informed public policy design in public administration (14).…”
Section: Introductionmentioning
confidence: 99%
“…Sensitive analysis of a big data driven versus a micro-data driven narrative analysis and policy interpretation remains a gap in the literature. While this study did not intend to address this gap, however, we test the practical efficacy of the proposed micro-dataset driven deep-narrative analysis in Debnath et al, (2020). Our meta-analysis based on the bibliographic dataset of the state-of-the-art literature in energy policy, narrative analysis, computational social science and topic modelling have shown that our nested methodology potentially enables in the cross-fertilisation of topic modelling and grounded theory-aided narrative-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Potential to identify key themes and topics that can inform policymakers' policies and decision making. [55]…”
mentioning
confidence: 99%